2005
DOI: 10.1159/000089242
|View full text |Cite
|
Sign up to set email alerts
|

Pitavastatin Prevents Bacterial Translocation after Nonpulsatile/Low-Pressure Blood Flow in Early Atherosclerotic Rat: Inhibition of Small Intestine Inducible Nitric Oxide Synthase

Abstract: Background: Cardiopulmonary bypass decreases intestinal mucosal blood flow because of nonpulsatile and low-pressure blood flow resulting in bacterial translocation (BT) and atherosclerosis also has peripheral blood flow deficiency. The risk of nonpulsatile and low-pressure blood flow for atherosclerotic animals and the effect of statin administration, which has pleiotropic effects, were studied. Methods: Wistar rats were divided into four groups: group N (normal diet), group C (high-cholesterol diet), group S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…It did not consider the doses or types of statins that patients were taking, nor did it account for the length of time patients had been on statins. Though our aim was to explore the class effect of statins, differences in the properties of individual statin drugs have been previously described [7,24,26]. The interval between the index operation and presentation with ASBO may also be a variable of interest but was unable to be calculated due to a lack of reliable data and patients having multiple operations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It did not consider the doses or types of statins that patients were taking, nor did it account for the length of time patients had been on statins. Though our aim was to explore the class effect of statins, differences in the properties of individual statin drugs have been previously described [7,24,26]. The interval between the index operation and presentation with ASBO may also be a variable of interest but was unable to be calculated due to a lack of reliable data and patients having multiple operations.…”
Section: Discussionmentioning
confidence: 99%
“…Statins may also reduce adhesions due to their antioxidant properties [23]. Moreover, statins have also been shown to reduce intestinal ischemia and reperfusion injury and decrease bacterial translocation and peritoneal inflammation [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies found that PGN induced the production of pro-inflammatory cytokines through TLR2 and increased the vulnerability of AS plaques (Nijhuis et al, 2004). While the vascular endothelial dysfunction appeared in rats modeled by surgery and a high-cholesterol diet, the concentration of serum PGN was significantly increased (Tsunooka et al, 2005). It has been confirmed that TLR2 is expressed in macrophages in AS lesions.…”
Section: Peptidoglycanmentioning
confidence: 94%
“…In this way it enhances monocyte adhesion and chemotaxis, that lead to vascular disease PGN recognition protein-1 (PGLYRP-1) which can also recognize PGN. It should be highlighted that high levels of PGLYRP-1 are associated with vascular disease and may favor the formation of atherosclerotic plaques by modulating the overexpression of adhesion molecules [ 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ].…”
Section: Cardiovascular Diseases and Periodontitismentioning
confidence: 99%